The Role of Memory T-Cell Mediated Immunity in Long-term COVID-19: Effects of Vaccination Status - Saulesh S. Kurmangaliyeva; Akzhan M. Madenbayeva; Saltanat T. Urazayeva; Yerlan Sh. Bazargaliyev; Khatimya I. Kudabayeva; Kairat B. Kurmangaliyev (Iranian Journal of Medical Sciences)
T-cell-mediated immunity is essential for controlling severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) infection, preventing severe disease, and potentially reducing the risk of long-term coronavirus disease (COVID). This study investigated the impact of natural infection, vaccination, and hybrid immunity on T-cell responses, with a particular emphasis on the role of memory T-cells in long-term COVID-19. The present study reviewed current literature on T-cell responses, including memory T-cell development, in individuals with natural SARS-CoV-2 infection, those vaccinated with messenger RNA (mRNA) vaccines, and those with hybrid immunity. It examined studies that compared T-cell activity, immune regulation, and the prevalence of long-term COVID-19 across these groups. Natural infection induces variable T-cell responses, with severe cases showing stronger but sometimes dysregulated immunological activity, which may contribute to prolonged COVID-19. Vaccination, particularly with mRNA vaccines, elicits targeted and consistent T-cell responses, including memory T-cells, reducing disease severity, and the incidence of long-term COVID-19. Hybrid immunity combines natural infection and vaccination, provides the most robust protection, enhanceds memory T-cell responses, and reduces the risk of long-term COVID-19 through balanced immune regulation. Memory T-cells play a critical role in mitigating long-term COVID-19. Vaccination significantly enhances T-cell-mediated immunity, minimizing the risk of chronic symptoms compared to natural infection alone. Hybrid immunity provides the most effective defense, emphasizing the importance of vaccination, even after natural infection, to prevent long-term COVID-19.